A Signal of (Train)Ability? Grade Repetition and Hiring Chances - Stijn Baert; Matteo Picchio (Institute of Labor Economics (IZA), 2020)
This article contributes to the nascent literature on the effect of grade retention in school on later labour market success. A field experiment is conducted to rule out the endogeneity of both outcomes. More concretely, various treatments of grade retention are randomly assigned to fictitious résumés sent in application to real vacancies. Overall, grade retention does not significantly affect positive call-back by employers. However, when narrowing in on vacancies for occupations where on-the-job training is important, job candidates with a record of grade retention are 16% less likely to receive a positive reaction. This finding is consistent with Queuing theory.
Keywords: I21; J23; J70; C93; 330; grade retention; hiring youth; training; signalling; queuing